Secure communication optimization for double-IRS assisted SWIPT system - Jianfeng CHEN; Miao CUI; Guangchi ZHANG; Qingqing WU; Hui ZENG (Dianxin kexue)
Two intelligent reflecting surfaces (IRS) was applied to ensure the physical layer security of the information transmission in a simultaneous wireless information and power transfer (SWIPT) system, where a multi-antenna base station (BS) simultaneously transmits information and energy to multiple single-antenna information receivers (IR) and energy receivers (ER) and the ERs are regarded as potential information eavesdroppers.The system deploys two IRSs to ensure the security of information transmission while meeting the requirements of energy transmission.Due to the inter-IRS signal reflection, the variables of the considered optimization problem are highly coupled, thus the problem is difficult to solve.To tackle this difficulty, an algorithm based on the alternating optimization, semidefinite relaxation, and successive convex approximation methods was proposed to obtain a suboptimal solution to the problem.Simulation results show that the proposed algorithm can significantly increase the total rate of the IRs and guarantee the security of the information transmission and the requirement of energy transmission, as compared to some existing benchmark schemes.